Pengaruh Pelapisan Kitosan pada Resin Komposit Nanohybrid pada Perendaman Kopi (coffea sp.) terhadap Perubahan Warna: The Effect of Chitosan Coating on Nanohybrid Composite Resin in Coffee (Coffea sp.) Soaking on Color Changes - Mara Gustina; Siti Aisyah; Achmad Junaidi; Eka Efrata; Rudy S; Herautami Setiawati; Dimas Wicaksono (Bhakta Dental Journal, 2026)
Background: Composite resin is a material used as a restoration treatment that is the same color as teeth. Color changes in composite resin can be reduced by adding edible coating. Edible coating can be made from polysaccharides, proteins, and lipids. Objective: To determine the effect of chitosan coating on nanohybrid composite resin in coffee immersion on color changes. Method: Laboratory experimental research, with a posttest only control group design. The study consisted of 3 groups, namely 5 negative controls, 5 positive controls, 5 treatment controls that were given a 1% chitosan coating with immersion for 5 minutes. Each positive control group, negative control group and treatment group were soaked in coffee solution for 7 days. Results: In the negative control it was 15.3080 mV, the positive control was 23.0980 mV, the treatment group was 28.4960 mV. Conclusion: There is a significant difference in color changes between nanohybrid composite resin coated with chitosan and uncoated, indicating that chitosan has the potential as a coating material against dyes from coffee. Keywords: Chitosan, Nanohybrid Composite Resin, Color Change